2016
DOI: 10.1007/s12079-016-0355-5
|View full text |Cite
|
Sign up to set email alerts
|

FAT4 hypermethylation and grade dependent downregulation in gastric adenocarcinoma

Abstract: Gastric cancer is one of the major causes of death due to cancer in the world. It is a multi-factorial disease with epigenetic factors being also involved in its development. FAT4 is a tumor suppressor gene exerting an important role in cell adhesion. This study aimed at analyzing FAT4 expression and promoter methylation in gastric cancer. FAT4 expression was studied in 30 tumoral tissues and their non-tumoral counterparts using Taqman real time PCR method. Promoter methylation was assessed using bisulfite con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…These cell adhesion molecules interact in a heterophilic manner to initiate bidirectional signaling (hereafter Fat signaling), mediated by their cytoplasmic domains to regulate a number of critical developmental processes including growth, tissue patterning, convergent extension and directed cell migration. Mutations in FAT4 and DCHS1 are associated with many cancers and multi system developmental defects such as Van Maldergem syndrome and Hennekam syndrome, characterized by craniofacial anomalies, intellectual dysfunction, digital contractures, hypoplastic kidneys, sternal and auditory defects ( Cappello et al, 2013 ; Alders et al, 2014 ; Hou et al, 2016 ; Ma et al, 2016 ; Pilehchian Langroudi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…These cell adhesion molecules interact in a heterophilic manner to initiate bidirectional signaling (hereafter Fat signaling), mediated by their cytoplasmic domains to regulate a number of critical developmental processes including growth, tissue patterning, convergent extension and directed cell migration. Mutations in FAT4 and DCHS1 are associated with many cancers and multi system developmental defects such as Van Maldergem syndrome and Hennekam syndrome, characterized by craniofacial anomalies, intellectual dysfunction, digital contractures, hypoplastic kidneys, sternal and auditory defects ( Cappello et al, 2013 ; Alders et al, 2014 ; Hou et al, 2016 ; Ma et al, 2016 ; Pilehchian Langroudi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, TGFβ1 molecule produced by stromal cells can impart an important role in regulating microenvironmental bystander effects. [65][66][67][68][69] The role of this molecule in three processes of maintaining tissue stability, responding to radiation, and developing bystander effect further confirms a link between the bystander effect and the microenvironmental response to radiation.…”
Section: Radiation Microenvironment and Carcinogenesismentioning
confidence: 67%
“…Through Gene Expression Analysis, we speculated that FAT4 was a tumor suppressor gene. Studies suggested FAT4 expression was reduced in gastric adenocarcinoma and hepatocellular carcinoma tumor tissues, and FAT4 downregulation was associated with tumor grade ( 11 , 12 ). Functional analysis using RNAi-mediated knockdown of FAT4 revealed an increased cancer cell growth and proliferation, suggesting the putative tumor suppressor role of FAT4 in hepatocellular carcinoma cancer ( 12 ).…”
Section: Discussionmentioning
confidence: 99%